Global trade integration and outsourcing: how well is the EU coping with the new challenges - Havik, Karel; McMorrow, Kieran; European Commission : Directorate-General for Economic and Financial Affairs (Bruxelles- Luxembourg: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Even with the growing internationalisation of production and the emerging concerns regarding the outsourcing phenomenon, the present study suggests that Europe has handled the post-1990 upsurge in worldwide trade integration in a relatively successful way. The EU continues to retain its long-established title as the number 1 global trading power. In addition, the EU has been a net gainer in terms of the outsourcing part of the production relocation phenomenon, with an increase in its surplus on trade in intermediate goods and services over the period 1992 to 2003. However, despite this relatively reassuring assessment, the study also highlights a number of areas of concern, such as geographically with regard to the EU's growing trade deficits with Asia in general and technologically with the EU's exceptionally poor performance on the ICT front. Complacency must therefore be avoided and policy makers need to remain vigilant to a number of potential medium to long run challenges to the EU's present hegemony in world trade.
Economic Papers